The Importance of Effective HR Planning in Optimizing Organizational Performance - Bahiroh, Eloh (PT Larva Wijaya Penerbit, 2023)
Human Resources is an important pillar and at the same time a central asset in a company that needs to be managed properly and maturely. It is through HR that various visions, missions, goals and objectives of the company can be implemented, so that in other words it can be interpreted that human resources play an important role in the course of organizational activities. The initial stage in building good HR management practices is the human resource planning stage, this is the initial foundation in establishing an effective HR management process in an organization or company. Therefore, it is necessary to have an in-depth understanding of the company's HR managers in understanding the systematics of good and correct HR planning. For this reason, this article aims to examine the importance of effective HR planning in shaping optimal organizational performance. The use of the method in this article is a descriptive method with a literature study approach based on related literature to strengthen the arguments in this article. So that this article is made as a basis in providing arguments regarding proper HR planning to be implemented by an organization or company in terms of managing its human resources so that optimal organizational performance can be created which has an impact on achieving organizational goals and objectives.